Combining thio-bromo Click chemistry and raft polymerization: a powerful tool for preparing functionalized multiblock and hyperbranched polymers - Xu, J.; Tao, L.; Boyer, C.; Lowe, Andrew; Davis, T. (American Chemical Society, 2010)
An experiment was conducted to prove that RAFT-prepared polymers can serve as convenient masked macromolecular thiols suitable for thio-bromo reactions. Homopolymers were prepared by RAFT polymerization using 4-cyanopentanoic acid dithiobenzoate (CPADB) as the chain transfer agent, yielding homopolymers with dithiobenzoate groups at the ?-termini that can be readily cleaved to thiols through aminolysis. The aminolysis of PMA4500 in the presence of MBP was performed using hexylamine/triethylamine (TEA) as the cleavage agent and base, respectively, in a molar ratio PMA4500/hexylamine/TEA/MBP=1/1/2/2 in acetonitrile at a concentration of 0.027 mol/L. A small shift to lower retention time was observed for the MBP modified PMA4500. The appearance of a small fraction of coupled products compared to the parent PMA4500 homopolymer. PMA1000 was aminolyzed in the presence of MBP or EBiB and the products analyzed by ESI mass spectrometry (MS) to verify successful cleavage/thioether formation.